KARAKTERISTIK PENGGUNA GIGI TIRUAN DENGAN PEMANFAATAN JASA TUKANG GIGI - Mega Silvia; Suharyono Suharyono; Ta’adi Ta’adi (Journal of Oral Health Care, 2014)
Manufacture and installation of denture teeth not only a dentistworking area but also services of builders teeth and nowmany services of builders teeth medical practice under thestandards so as to endanger the public . Although considereddangerous , there are still many people who use the servicesof builders teeth than dentists. Making use of dentures withdental handyman services can be influenced by the characteristicsof the denture user community that includes education, occupation , income , level of knowledge , and beliefs .Based on preliminary studies in Kenagarian Sijunjung ,Sumatera Barat on March 2013 with interviewsobtained datafrom forty people who wear dentures only six people who weardentures with dental services utilization and the rest wore dentureswith dental utilization handyman services. This studyaims to determine the relationship of user characteristics withthe use of denture teeth handyman services. This type of observationalanalytic study to analyze a situation with crosssectionalresearch design. Study location in KenagarianSijunjung,Sumatera Barat. The study subjects were users ofdenture teeth with the use of handyman services.Purposivesampling using a sampling technique. Sample of large is thirtypeople. Data collection techniques are the interview questionsbased on the questionnaire. Analysis of data using SpearmanRho correlation statistical test with significance standard 0.05.Spearman Rhoresult of the user relations characteristics ofhip with the use of denture teeth handyman services for theeducation variables are not significant correlation ( ? = 0.941,? > 0.05 ) , there is no job variables significant correlation( ? = 0.521, ? > 0.05 ) , income variables are not significantcorrelation ( ? = 0.797, ? > 0.05), variable levels of knowledgethere is significant correlation ( ? = 0.047, ? < 0.05),and there is a belief variables significant correlation ( ? =0.045, ? > 0.05)